1D Confocal Broad Area Semiconductor Lasers (Confocal BALs) for Fundamental Transverse Mode Selection (TMS#0). (17th June 2019) - Fouckhardt, Henning; Kleinschmidt, Ann-Kathrin; Strassner, Johannes; Doering, Christoph
Abstract : Previously in this journal we have reported on fundamental transverse mode selection (TMS#0) of broad area semiconductor lasers (BALs) with integrated twice-retracted 4 f set-up and film-waveguide lens as the Fourier-transform element. Now we choose and report on a simpler approach for BAL-TMS#0, i.e., the use of a stable confocal longitudinal BAL resonator of length L with a transverse constriction. The absolute value of the radius R of curvature of both mirror-facets convex in one dimension (1D) is R = L = 2 f with focal length f . The round trip length 2 L = 4 f again makes up for a Fourier-optical 4 f set-up and the constriction resulting in a resonator-internal beam waist stands for a Fourier-optical low-pass spatial frequency filter. Good TMS#0 is achieved, as long as the constriction is tight enough, but filamentation is not completely suppressed.